Pengabdian Kepada Masyarakat Melalui Program “Sekolah Bina Cerah” Pada SDN Sumurmati I - Anggara Putra Bimantara; Yanda Bara Kusuma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Based on the results of a survey conducted by KKN-T MBKM Group 62 students, there were only 10 MSME actors in Sumurmati Village. With the